Bioinspired Smart Actuator Based on Graphene Oxide-Polymer Hybrid Hydrogels - Wang, Tao; Huang, Jiahe; Yang, Yiqing; Zhang, Enzhong; Sun, Weixiang; Tong, Zhen (ACS applied materials & interfaces, 2015)
Rapid response and strong mechanical properties are desired for smart materials used in soft actuators. A bioinspired hybrid hydrogel actuator was designed and prepared by series combination of three trunks of tough polymer–clay hydrogels to accomplish the comprehensive actuation of “extension–grasp–retraction” like a fishing rod. The hydrogels with thermo-creep and thermo-shrinking features were successively irradiated by near-infrared (NIR) to execute extension and retraction, respectively. The GO in the hydrogels absorbed the NIR energy and transformed it into thermo-energy rapidly and effectively. The hydrogel with adhesion or magnetic force was adopted as the “hook” of the hybrid hydrogel actuator for grasping object. The hook of the hybrid hydrogel actuator was replaceable according to applications, even with functional materials other than hydrogels. This study provides an innovative concept to explore new soft actuators through combining response hydrogels and programming the same stimulus.